2005
DOI: 10.1530/eje.1.01930
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender, age and renal function on plasma adiponectin level: the Tanno and Sobetsu study

Abstract: Design: The aim of this study was to determine the association between aging and adiponectin level from the aspect of the influence of renal function and sex hormones in humans. Methods: Serum adiponectin and blood urea nitrogen (BUN) levels were measured in 964 subjects (372 males) aged 60.3^12.5 years. Testosterone and free testosterone levels were measured in 123 males, and estrone and estradiol levels were measured in 114 females. The subjects were divided into two age groups; 65 years of age or older (Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
125
3
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(154 citation statements)
references
References 34 publications
21
125
3
5
Order By: Relevance
“…Adipocyte culture, animal and human studies consistently point to a suppressive effect of testosterone on serum adiponectin. However, a recent study of 123 Japanese men reported a positive relation between total testosterone levels and serum adiponectin, 33 consistent with our results. The inverse relation between endogenous estrogen and adiponectin has been observed previously in two smaller studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Adipocyte culture, animal and human studies consistently point to a suppressive effect of testosterone on serum adiponectin. However, a recent study of 123 Japanese men reported a positive relation between total testosterone levels and serum adiponectin, 33 consistent with our results. The inverse relation between endogenous estrogen and adiponectin has been observed previously in two smaller studies.…”
Section: Discussionsupporting
confidence: 93%
“…One Japanese study reported weak positive correlations between adiponectin and serum creatinine and BUN in 352 women, 45 whereas another reported positive relations for BUN, but not creatinine, in both sexes. 33 Calculated glomerular filtration rate was inversely related to adiponectin in a group of 125 Polish men and women when analyzed together; however, serum creatinine did not contribute significantly to adiponectin levels in sexspecific multivariate analyses. 46 In this cohort, evidence that age-related deterioration of kidney function contributes to higher circulating levels in older adults was weak; adiponectin was not related to serum creatinine in either sex, before or after adjusting for covariates, and was associated with BUN in men only.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We found that the age, gender, insulin resistance and plasma levels of TG, HDL-C, BNP and uric acid influenced the adiponectin level in all participants, which agreed with previous reports. 5,24,25 However, we found that the glucose spike during the OGTT did not affect the plasma adiponectin level, although HOMR-IR (which represents insulin resistance) had an influence on adiponectin. The present results suggest that adiponectin may have a regulatory role in insulin secretion.…”
Section: Discussionmentioning
confidence: 59%
“…Firstly, a small decline in renal function was found to be associated with increased adiponectin in subjects 65 years and older compared with subjects younger than 65 years. 46 It has also been hypothesized that adiponectin increases as a compensatory mechanism to minimize IR in older adults and restore metabolic normality. 47 Recently, adiponectin resistance at the skeletal muscle has been shown to occur in humans with chronic heart failure.…”
Section: Gender Age Mets and Adiponectinmentioning
confidence: 99%